Flooded boxcar camp - Thomas Hart Benton (artist):::Creator:::::::::::: (2024)
The flooded boxcar camp from The Grapes of Wrath, vol.2, p. 536, illustrated edition. Thomas Hart Benton, a native of eastern Oklahoma, was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate. "In the boxcar camp the water stood in puddles and the rain splashed in the mud. Gradually the little stream crept up the bank toward the low flat where the boxcars stood."